2016
DOI: 10.5194/tc-10-2611-2016
|View full text |Cite
|
Sign up to set email alerts
|

Concentration, sources and light absorption characteristics of dissolved organic carbon on a medium-sized valley glacier, northern Tibetan Plateau

Abstract: Abstract. Light-absorbing dissolved organic carbon (DOC) constitutes a major part of the organic carbon in glacierized regions, and has important influences on the carbon cycle and radiative forcing of glaciers. However, few DOC data are currently available from the glacierized regions of the Tibetan Plateau (TP). In this study, DOC characteristics of a medium-sized valley glacier (Laohugou Glacier No. 12, LHG) on the northern TP were investigated. Generally, DOC concentrations on LHG were comparable to those … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
62
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 55 publications
6
62
1
2
Order By: Relevance
“…A lack of OC consideration due to the limitation of the SNICAR model also affected the results in this study. Due to its light-absorbing properties (Andreae and Gelencsér, 2006;Bahaur et al, 2012;Yan et al, 2016), OC in snow cover can also absorb solar radiation and reduce the surface albedo. Previous studies indicated that OC was responsible for more than 10-40 % of the light absorption Doherty et al, 2010;Lin et al, 2014;Wang et al, 2015).…”
Section: Limitations and Implications For Snow Cover And Glaciers On mentioning
confidence: 99%
See 1 more Smart Citation
“…A lack of OC consideration due to the limitation of the SNICAR model also affected the results in this study. Due to its light-absorbing properties (Andreae and Gelencsér, 2006;Bahaur et al, 2012;Yan et al, 2016), OC in snow cover can also absorb solar radiation and reduce the surface albedo. Previous studies indicated that OC was responsible for more than 10-40 % of the light absorption Doherty et al, 2010;Lin et al, 2014;Wang et al, 2015).…”
Section: Limitations and Implications For Snow Cover And Glaciers On mentioning
confidence: 99%
“…Light-absorbing OC in snow can contribute significantly to the absorption of ultraviolet/visible light (Andreae and Gelencsér, 2006;Yan et al, 2016). Bahadur et al (2012) studied aerosol optical properties derived from the Aerosol Robotic Network (AERONET) measurements and estimated that, in California, the OC absorption at wavelength of 440 nm was approximately 40 % of the BC absorption.…”
mentioning
confidence: 99%
“…Mountain glaciers and ice sheets cover 11% of the land surface on Earth and store 6 petagrams of organic carbon (OC), the majority of which is WSOC (Hood et al, 2015;Yan et al, 2016). Global warming and glacier mass loss *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…WSOC has been proven to be absorbing sunlight at ultraviolet wavelengths (200-800 nm) (Andreae and Gelencser, 2006;Chen and Bond, 2010;Cheng et al, 2011;Bosch et al, 2014;Li et al, 2016a), and the radiative forcing caused by WSOC was estimated to account for 2-10% relative to black carbon (BC) in atmospheric aerosols in a typical pollution area of North China (Kirillova et al, 2014a) and about 10% at Laohugou (LHG) glacier, northern Tibetan Plateau (TP) (Yan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation